Молитовний дискурс поезії Тараса Шевченка - Семенюк, Лариса; Semeniuk, Larisa (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті показано молитовний лад Шевченкової поезії як вияв глибокої релігійності, чутливості поета, прояв його вболівання за долю України та його народу. Наголошено особливе місце в молитовному дискурсі поета творів періоду «трьох літ». В їх основі – віра в остаточну Господню волю, його милість до всіх людських благань. Благальні молитви нерідко завершуються мотивами прославлення Бога-спасителя та висловлення йому глибокої покори і вдячності. Звертаючись до Бога, Шевченко переважно виступає як «всенародний речник». This article shows the prayer motif in Shevchenko’s poetry to be an expression of his deep religiosity and sensitivity, and his deep concern about the fate of Ukraine and its people. It must be emphasized that Shevchenko possessed authentic spiritual roots and was imbued with beatific ideas regarding the Scripture. Many of his works are based on Christian prayers, which are an expression of the pious feelings of the poet and his communication with God regarding the problems of daily life, as well as an illustration of his literary and artistic techniques. The motif of prayer runs through Shevchenko’s poetry all the way from his first poems, which found expression in Kobzar in 1840, to his last works, which were written after his exile. The works of his «Three years» period occupy a special place in the poet’s prayerful discourse as he was passing through a strong ideological revolution. In his renderings of the Psalms of David, the poems. To the dead and the living, and the unborn ..., Heretic the author is full of faith in God, hope in Him, and hope in the power of the Lord's laws. In terms of their content, the majority of Shevchenko’s prayer poems can be treated as General l.-s. They are based on a belief in the finality of the Lord's will, and His mercy in response to all human entreaties. Prayers of pleading often end with an apotheosis of God and express deep humility and gratitude to Him. While appealing to God, Shevchenko as a rule does not talk about his personal feelings, but rather about nationwide misfortunes and problems, so he acts as a representative of his nation.
Prayer discourse in Taras Shevchenko’s poetry
Keywords: Тарас Шевченко; молитва; «Псалми Давидові»; переспів; вірш; поема; релігійність; Бог; Taras Shevchenko; prayer; the Psalms of David; rehash; God; poem; religiosity